Quantitative determination of the iron chelating agent Deferaserux and one of its process-related substance by using high performance liquid chromatography - هارون محمد (Latakia University Journal -Medical Sciences Series, 2023)
Deferasirox is an iron-chelating agent indicated in the treatment of chronic iron overload. This work aims to develop a new validated sensitive RP-HPLC coupled with a UV detector for the determination of Deferasirox and one of the unstudied impurities. The separation was achieved on the Kromosil C8 column (length of 250mm, internal diameter of 4.0 mm, and 5-μm particle size) at a temperature of 25℃. Phosphate Buffer and acetonitrile were used as a mobile phase by isocratic mode at a 0.8 mL/min flow rate. A wavelength of 254nm was selected to perform detection using a photodiode array detector. The method met the requirement of the International Conference on Harmonisation requirement for validation for the Registration of Pharmaceuticals for Human Use (ICH). The limit of detection (LOD) for Deferasirox was found to be 5.59 ng/mL and 8.35 ng/mL for the impurity DRS-1. The developed method was then tested by analyzing some samples of active pharmaceutical ingredients. The Impurity DRS-1 exceeded the impurities’ acceptable limits (0.1%) in one of these samples.